Psychological Well-Being of Young Athletes as a Condition for Further Career Development - Aigerim Zhunussova; Zhanat Aubakirova; Usha Subba (Insight: the psychological dimensions of society, 2025)
The aim of this study was to assess differences in the structure of psychological well-being of students of different sports specializations. This comparative analysis addresses a gap in current research by examining athletes in individu al combat sports (boxing, wrestling) and a team sport (hockey). Methods. The study involved 84 1st year students of the Academy of Physical Education and Mass Sports (Astana, Kazakhstan) in the specialties of “boxing” (28 people), “freestyle wrestling” (28 people), and “hockey” (28 people). Psychological well-being was measured using a modified version of K. Ryff’s Scales, which assesses six key dimensions. For correlation analysis, academic performance and career success were determined using document analysis and expert assessment. Results. Two significant differences were identified between student-wrestlers and student-boxers in the parameters of openness to new experiences (U = 305; p = .02) and personal growth (U = 332; p = .03). The study also revealed significant differences between student-hockeytive relationships with others (U = 321; p = .04) and autonomy (U = 312; p = .03). Statistical analysis also revealed significant differences between student-boxers and student-hockey players regarding positive relationships with others (U = 122; p = .04), openness to new experiences (U = 302; p = .02), and autonomy (U = 218; p = .02). The study confirmed a correlation between athletes’ psychological well-being and their academic performance, as well as their success in a sports career. Discussion and Сonclusions. On average, all indicators across the groups fell within the normal range; however, a third of the respondents showed a low level of the PW index and emotional balance. The study confirmed that the structure of personal psychological well-being among students involved in different sports disciplines has specific features. This may be useful for further work on students' psychological well-being. However, these differences proved to be insignificant when examining the relationship between psychological well-being and academic performance or career success.players and student-wrestlers in terms of posi